Profile of Phenolic Compounds and Phenol-Degrading Bacterial Colonies in Secondary Peat Forest Soil - Fiko Jervannes; Gusti Z. Anshari; Evi Gusmayanti; Yulita Andriyani (Jurnal Biodjati, 2025)
Peat contains high levels of phenols and lignin, which are resistant to decomposition. Drainage canals lower the groundwater table, promoting microbial degradation. This study investigated microbial decomposition in a secondary peat swamp forest by quantifying phenol-degrading bacterial colonies and measuring phenol concentrations in peat soil from Malikian Village, Mempawah Regency, West Kalimantan. Samples were collected from three plots at two depths, the aerobic layer and the anaerobic layer, with fifteen (15) samples from each depth. Bacterial colonies were counted via mineral salt medium (MSM) with up to five dilutions, whereas phenolic compounds were measured via the Folin–Ciocalteu method. Paired t-tests revealed highly significant differences in both phenol concentration (p-value < 0.001) and the number of phenol-degrading bacterial colonies (p-value < 0.003) between the aerobic layer and the anaerobic layers. These findings indicate that peat decomposition is more pronounced in the aerobic surface layer than in the permanently waterlogged layer. This observation is attributed to the greater number of phenol-degrading bacterial colonies and lower phenol concentration in the surface layer than in the deeper layer. Consequently, the aerobic conditions in the surface layer of the secondary peat swamp forest facilitate accelerated peat decomposition